Measurement of dabigatran, rivaroxaban and apixaban in samples of plasma, serum and urine, under real life conditions: an international study - Harenberg, Job; Wehling, Martin; Weiß, Christel; Krämer, Roland (Clinical chemistry and laboratory medicine, 2016)
Background: The utility of measuring non-vitamin K antagonist oral anticoagulants (NOACs) in plasma, serum and urine samples and with the point-of-care test (POCT) on urine samples should be analysed in an international laboratory study. Methods: The study was performed to determine the inter-laboratory variance of data from two chromogenic assays each for the NOACs rivaroxaban, apixaban and dabigatran, and to analyse the sensitivity and specificity of the POCT assays for factor Xa- and thrombin inhibitors. Plasma, serum and urine samples were taken from six patients in each group on treatment with a NOAC. Results: The inter-laboratory variances, which can be identified best by the coefficient of variation, ranged from 46% to 59% for apixaban, 63% to 73% for rivaroxaban and 39% to 104% for dabigatran using plasma, serum or urine samples and two chromogenic assays for each NOAC. The concentrations were about 20% higher in serum compared to plasma samples for apixaban and rivaroxaban, and 60% lower for dabigatran. The concentration in urine samples was five-fold (apixaban), 15-fold (rivaroxaban) and 50-fold (dabigatran) higher. Sensitivity and specificity of POCT for apixaban, rivaroxaban, and dabigatran were all >94%. Conclusions: The inter-laboratory study showed the feasibility of measurement of apixaban, rivaroxaban, and dabigatran in plasma, serum and urine samples of patients on treatment. Dabigatran was determined at far lower levels in serum compared to plasma samples. Concentrations of NOACs in urine were much higher compared to plasma. The POCT was highly sensitive and specific for all three NOACs